Development of NIE networks' nodal controller project to deliver reactive power support to the wider electricity system. Issue 18 (10th July 2019) - Pollock, Jonathan; Hill, David; Smyth, Lee; McGuckin, Donal
Abstract : In 2017, 34.8% of total electricity consumption in Northern Ireland was generated from renewable sources located in Northern Ireland. Alongside other significant changes to the electricity sector this leads to an increasing need for reactive power. This paper provides an overview of NIE Networks' nodal controller project which aims to deliver reactive power support to the wider system through the utilisation of Distributed Energy Resources (DERs). The requirements and implementation of the nodal controller are outlined with future work proposed to provide additional reactive power support to the system.